Identifying Barriers and Facilitators to Scalp Cooling Therapy Through a National Survey of the Awareness, Practice Patterns, and Attitudes of Oncologists. Issue 2 (February 2022) - Novice, Madison; Novice, Taylor; Henry, N. Lynn; Johnson, Kyle; Jeruss, Jacqueline S.; Kidwell, Kelley M.; Burness, Monika L.
Abstract : PURPOSE: Scalp cooling therapy (SCT) is the most effective method to reduce chemotherapy-induced alopecia (CIA), a highly distressing side effect of cancer treatment. Despite data supporting SCT efficacy and safety, SCT use in the United States is not widespread. Oncologists' interactions with scalp cooling were examined to identify facilitators and barriers to SCT implementation. METHODS: A 33-question survey was distributed through the ASCO Research Survey Pool to a nationally representative, random sample of 600 oncology providers. Outcome measures included knowledge of SCT, frequency of initiating conversations about SCT with patients, degree of support, and barriers for SCT. Significance was defined as P < .001. RESULTS: Of 155 (25.8%) responding providers, 62% of providers were in favor of SCT always or most of the time, but only 26% reported initiating discussions about SCT always or most of the time. Providers who treat breast cancer ( P ⩽ .0001), those who report being very familiar with SCT ( P ⩽ .0001), those who report having read SCT literature in the past 2 years ( P ⩽ .0001), and those who work at a facility with machine SCT ( P ⩽ .0001) were significantly more likely to initiate conversations with patients about SCT. Financial concerns (58%) were the primary reason for not recommending SCT use; efficacy (31%), staff or facility (24%), and safety (15%) concerns were also noted. Although safety concerns have decreased markedly over time, 14% of providers report patients who continue to express these concerns and 17% of providers see safety issues as barriers to supporting SCT. CONCLUSION: Our findings suggest that oncology provider familiarity and experience with SCT lead to increased support for scalp cooling, which may ultimately result in greater availability and utilization of SCT when indicated.